Cap +1 mutation; an unsuspected cause of beta thalassaemia transmission in Pakistan - Sadia Usman Babar; Moinuddin Moinuddin; Muhammad Usman Abdul Karim (Turkish Journal of Hematology, 2009)
Objective: Thalassemia is one of the most common genetic disorders worldwide. Cap +1 mutation which causes ‘silent beta thalassemia’ is present around all ethnic groups of Pakistan. This study was designed to detect the frequency of Cap+1 mutation in Pakistani Population.Materials and Methods: Molecular genetic for Cap+1 beta thalassemic mutation was done by extracting DNA from whole blood by using Genomic DNA Purification Kit (Gentra system USA). Amplification Refractory Mutation System (ARMS) primers were designed for detection of normal and mutant DNA.Basic hematological parameters were performed by using automated analyzer (Sysmex KX-21). Cellulose acetate hemoglobin electrophoresis was done by using semi-automated technique (INTERLAB Roma Microtech Series Electrophoresis system 4.23). Results: The frequency of Cap+1 mutation was observed 5% (10/200) in targeted thalassemic families (having patients with beta-thalassemia intermedia) while its frequency was observed 2% (12/600) in total thalassemic genes in Pakistani population. Conclusion: Cap+1 (A-C) is a silent mutation and it has very minimum effect on beta globin synthesis because of which it produces very less clinical severity and certain important laboratory diagnostic tests like basic hematological parameters and Hb A2 levels are also remain in normal range. Therefore individuals with Cap+1 mutation may produce children with beta-thalassemia intermedia if they marry an individual with beta-thalassemia minor. Cap+1 (A-C) mutation is an unsuspected cause of beta thalassemia transmission in Pakistani population. This mutation can identify at molecular level. As this molecular defect is difficult to diagnose in Laboratory with routine laboratory tests because of that it has become a serious hindrance for thalassemia prevention program in Pakistan.